An empirical study of e-participation in Social Movement Organisations. (9th December 2008) - Sudulich, Maria Laura
The widespread diffusion of Information and Communication Technologies (ICTs) has had a significant impact on European society. This study analyses the impact of ICT enabled political participation by Social Movement Organisations (SMOs). A sample of European protest networks and pressure groups' websites are analysed through the use of indicators that measure their ability to disseminate information, their potential for bilateral/multilateral communication, and their website connectivity. We found no significant differences in communication patterns between SMOs that have different sizes with regards to the information dissemination and communication patterns, and found that larger SMOs have more website connectivity.